Conrad Detrez - la belgitude en «je» et en jeu - Pantkowska, Agnieszka (Studia Romanica Posnaniensia, 2004)
Conrad Debrez is one of those Belgian writers in whom „the Belgitude" (being Belgian), or to put it differently, a relation to Belgium, characteristic of the writers of the 70s of the 20th century, is full of contradictory and intermingled feelings and emotions, from love to disdain, has found its fullest expression. It is suggested that in his case, the attitude to homeland, and therefore, to his own identity, should be traced on the basis of his autobiographical trilogy where a peculiar play with „I" is in fact an attempt at solving the problem of a Belgian's identity.